Magnetic levitation (design PID controller) - Noriah Jaafar
Magnetic levitation systems, based on electromagnetism, are characterized by open loop instability and non linear dynamics are described by highly nonlinear equations that suggest the need of stabilizing controllers which will be design in this project using the MATLAB simulation.